2016
DOI: 10.1080/15548627.2016.1245261
|View full text |Cite
|
Sign up to set email alerts
|

Store-operated calcium entry-activated autophagy protects EPC proliferation via the CAMKK2-MTOR pathway in ox-LDL exposure

Abstract: Improving biological functions of endothelial progenitor cells (EPCs) is beneficial to maintaining endothelium homeostasis and promoting vascular re-endothelialization. Because macroautophagy/ autophagy has been documented as a double-edged sword in cell functions, its effects on EPCs remain to be elucidated. This study was designed to explore the role and molecular mechanisms of store-operated calcium entry (SOCE)-activated autophagy in proliferation of EPCs under hypercholesterolemia. We employed oxidized lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
55
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(58 citation statements)
references
References 69 publications
3
55
0
Order By: Relevance
“…As shown in Figure 4(c), in OGDtreated cortical neurons, the intracellular Ca 2+ level was significantly increased at the early stage of OGD, and returned to the basal level thereafter, which is consistent with a previous reports [46]. Furthermore, lines of evidence have indicated that intracellular Ca 2+ may regulate TFEB phosphorylation at least in part through the PPP3/calcineurin signaling pathways [47,48], especially in autophagy [29]. These data suggest the possibility that the intracellular Ca 2+ -dependent PPP3/calcineurin pathway may be an upstream regulator of TFEB function at the early stage of ischemia.…”
Section: Discussionsupporting
confidence: 90%
“…As shown in Figure 4(c), in OGDtreated cortical neurons, the intracellular Ca 2+ level was significantly increased at the early stage of OGD, and returned to the basal level thereafter, which is consistent with a previous reports [46]. Furthermore, lines of evidence have indicated that intracellular Ca 2+ may regulate TFEB phosphorylation at least in part through the PPP3/calcineurin signaling pathways [47,48], especially in autophagy [29]. These data suggest the possibility that the intracellular Ca 2+ -dependent PPP3/calcineurin pathway may be an upstream regulator of TFEB function at the early stage of ischemia.…”
Section: Discussionsupporting
confidence: 90%
“…Nevertheless, in our conditions, P-Akt(308) was not down-regulated by CAI. Furthermore, since one of the major targets of CamKK2 is AMPK protein, it could be hypothesized that decreasing calcium could lead to a down-regulation in the CamKK2/AMPK pathway and consequently to an up-regulation of mTORC1, as previously described [ 69 , 70 ]. Nonetheless, the contrary result we obtained implies that calcium/CamKK2 is not the main pathway targeted by CAI and that CamKK2 is not involved in mTORC1 and Mcl-1 down-regulation.…”
Section: Discussionmentioning
confidence: 94%
“…Yang et al found that proliferation of endothelial progenitor cells can be inhibited obviously by ox-LDL at concentration 30-100 mg/L after 12 h exposure. [36][37][38][39][40] However, report also indicates that ox-LDL can enhance cell proliferation in human aortic smooth muscle cells or Endothelial cell at a relatively low concentration. [41][42][43][44] This difference might be due to cell performance differs to cell type when expose to ox-LDL.…”
Section: Discussionmentioning
confidence: 99%